Kontruksi Graf Pengetahuan pada Direktori Perusahaan menggunakan Basis Data Graf Neo4j - Prataba, Guruh Dewa; Putra, Yoga Cahya; Widodo, Eko Teguh (Seminar Nasional Official Statistics, 2024)
This study addresses the importance of integrating establishment directory data in Indonesia through the knowledge graph approach using Neo4j. Company directories, which contain basic information such as names, addresses, and Standard Classification of Indonesian Business Fields (KBLI) codes, are often dispersed across various formats and sources, making comprehensive data analysis challenging. This research proposes the use of knowledge graphs as a solution to overcome the limitations of data integration based on Relational Database Management Systems (RDBMS), highlighting the flexibility and efficiency of Neo4j in handling complex data and performing intuitive queries. Case studies in this research demonstrate that knowledge graphs can be used to identify significant patterns and relationships between establishment entities, aiding in industry mapping, regional economic planning, and supporting data-driven decision-making. However, the study also identifies challenges in data collection and transformation, which require further research to enhance the application of knowledge graphs in the future.